2021
DOI: 10.1111/maps.13618
|View full text |Cite
|
Sign up to set email alerts
|

Presolar stardust in highly pristine CM chondrites Asuka 12169 and Asuka 12236

Abstract: We report a NanoSIMS search for presolar grains in the CM chondrites Asuka (A) 12169 and A12236. We found 90 presolar O‐rich grains and 25 SiC grains in A12169, giving matrix‐normalized abundances of 275 (+55/−50, 1σ) ppm or, excluding an unusually large grain, 236 (+37/−34) ppm for O‐rich grains and 62 (+15/−12) ppm for SiC grains. For A12236, 18 presolar silicates and 6 SiCs indicate abundances of 58 (+18/−12) and 20 (+12/−8) ppm, respectively. The SiC abundances are in the typical range of primitive chondri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 52 publications
(171 reference statements)
4
29
0
Order By: Relevance
“…DOM 08006 is composed of an unequilibrated mixture of anhydrous silicates, metal, and sulfides (Davidson et al., 2019) and is classified as one of the most pristine meteoritic samples available for the study due to its lack of evidence of alteration processes. DOM 08006 contains one of the highest abundances of O‐rich presolar grains reported to date in meteorites (~257 ppm; Davidson et al., 2019; Haenecour et al., 2018; Nittler et al., 2018), similar to abundances reported in a recent study of Asuka 12169 (~236 ppm; Nittler et al., 2021). Raster ion imaging of select matrix regions and fine‐grained rims around chondrules was performed with the Cameca NanoSIMS 50 at Washington University in St. Louis and previously reported by Haenecour et al.…”
Section: Samples and Experimental Methodssupporting
confidence: 76%
“…DOM 08006 is composed of an unequilibrated mixture of anhydrous silicates, metal, and sulfides (Davidson et al., 2019) and is classified as one of the most pristine meteoritic samples available for the study due to its lack of evidence of alteration processes. DOM 08006 contains one of the highest abundances of O‐rich presolar grains reported to date in meteorites (~257 ppm; Davidson et al., 2019; Haenecour et al., 2018; Nittler et al., 2018), similar to abundances reported in a recent study of Asuka 12169 (~236 ppm; Nittler et al., 2021). Raster ion imaging of select matrix regions and fine‐grained rims around chondrules was performed with the Cameca NanoSIMS 50 at Washington University in St. Louis and previously reported by Haenecour et al.…”
Section: Samples and Experimental Methodssupporting
confidence: 76%
“…In general, CCs experienced less heating than OCs, although there are exceptions. More pertinent to this discussion is the relative heating of Semarkona as compared to the CCs investigated in previous TEM presolar grains studies, especially the highly unaltered ungrouped C2 Acfer 094 and CO3.0 Dominion Range (DOM) 08006 (Vollmer et al, 2009a;Nittler et al, 2018), which along with CM Asuka 12169 (Nittler et al, 2021), contain the highest abundances of presolar silicates of any chondrites. Grossman and Brearley (2005) found that both Semarkona and Acfer 094 are highly primitive (3.00), having escaped significant heating, as determined from the Cr contents of FeO-rich olivines in Type IIA chondrules.…”
Section: Parent Body Alterationmentioning
confidence: 99%
“…The grains are a subset of presolar grains identified by their highly anomalous C and/or O isotopic compositions during an automated NanoSIMS isotopic imaging search (Barosch et al, 2021) of the Semarkona thin section (UNM 102) first studied by Dobrică and Brearley (2020). The NanoSIMS mapping methods were essentially identical to that used by Nittler et al (2021) with a <150-nm Cs + beam being scanned over 10×10 m 2 areas with simultaneous detection of negative secondary ions of the C and O isotopes as well as 28 Si and 27 Al 16 O to aid in mineralogical characterization. Following their identification by automated imaging, the grains were re-located and analyzed for their Mg and Si isotopic ratios.…”
Section: Nanosims Isotopic Measurementsmentioning
confidence: 99%
“…Typical characteristics of mildly altered CM chondrites include pristine amorphous silicates and metal in the matrix, the retention of glassy mesostasis in chondrules, melilite‐bearing CAIs, and high presolar grain abundances (Chizmadia & Brearley, 2008; Hewins et al., 2014; Kimura et al., 2020; Lee et al., 2016; Leroux et al., 2015; Marrocchi et al., 2014; Nittler et al., 2021; Palmer & Lauretta, 2011; Rubin, 2015; Rubin et al., 2007; Vollmer et al., 2020). They often have lower bulk phyllosilicate and water contents and higher δD and δ 15 N values than more altered CM chondrites (Alexander et al., 2013; Garenne et al., 2014; Howard et al., 2015; Vacher et al., 2020), and several have oxygen isotopic compositions that either fall at the 16 O‐rich end of the CM field or overlap with the CV‐CK/CO fields (Ebert et al., 2019; Haack et al., 2012; Hewins et al., 2014; Howard, Benedix, Bland, Gibson et al., 2011; Kimura et al., 2020; Lee et al., 2016; Lee, Cohen, King & Greenwood, 2019).…”
Section: Introductionmentioning
confidence: 99%